2012
DOI: 10.1007/s00270-012-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan Loaded in Eluting Beads: Preclinical Assessment in a Rabbit VX2 Liver Tumor Model

Abstract: Compared with IV or IA, DEBIRI induces lower early serum levels of irinotecan, a high and prolonged intratumoral level of irinotecan, and a greater rate of tumor necrosis at 24 h. Further evaluation of the clinical benefit of DEBIRI is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In a rabbit liver tumor model, it was shown after injection of 40 mm ONCOZENE DEE agents loaded with irinotecan that time at the drug maximum concentration (C max ) was prolonged (7). This time period was longer than that reported with DC Bead (8).…”
mentioning
confidence: 93%
“…In a rabbit liver tumor model, it was shown after injection of 40 mm ONCOZENE DEE agents loaded with irinotecan that time at the drug maximum concentration (C max ) was prolonged (7). This time period was longer than that reported with DC Bead (8).…”
mentioning
confidence: 93%
“…Several microspheres loadable with IRI are now proposed: DC Bead ® (DC; Biocompatibles UK Ltd, London, United Kingdom), HepaSphere™ (HS; BioSphere Medical, Roissy-en-France, France), and TANDEM ® (CeloNova BioSciences, Newnan, Georgia). Preclinical trials evaluated the properties of the three products individually but not comparatively (12)(13)(14)(15)(16). One in vitro study suggested slight differences in the physical characteristics or elution properties of the different brands of microspheres (17).…”
mentioning
confidence: 98%
“…This fast initial elution of irinotecan has been previously described for DEBIRI (16). In a rabbit VX2 liver tumor model, Rao et al (18) observed the highest irinotecan plasma concentration after 10 minutes. By contrast, Tanaka et al reported that TANDEM had a prolonged C max (24).…”
Section: Discussionmentioning
confidence: 79%
“…Irinotecan inhibits the DNA topoisomerase (13) and is a prodrug with the active metabolite SN-38 (14,15). Several experimental studies have investigated the pharmacokinetics of irinotecan after chemoembolization with DEBIRI (16)(17)(18)(19)(20). Plasma irinotecan levels were 70%-75% lower after embolization with drug-eluting embolic agents than after intra-arterial administration of irinotecan (19).…”
Section: Discussionmentioning
confidence: 97%